Our father Abraham : Jewish roots of the Christian faith - Wilson, Marvin R., 1935- (Grand Rapids, Mich. : William B Eerdmans Publishing Company, 1989)
This manuscript was written with the hope that it will prove instrumental in pointing Christians of every denomination and ethnic background to the importance and richness of their Hebrew heritage.Our Father Abraham is an introduction to the world of Hebrew thought. It is intended primarily for Christians, but it is hoped that Jews may benefit from much of this book as well. Although this work is a biblical, historical, and cultural study, the reader will quickly find out that it is concerned with more than exploring the past
I A new people? Abraham's spiritual children : 1 The root and branches ; "look to Abraham your father" ; Athens or Jerusalem? ; The world of the Bible ; The olive root and branches ; Grafted into Israel ; 2 Gentiles, Jews, and Jewish heritage ; A new spiritual family ; Salvation by grace or works? A new terminology ; Gentile and Christian are not synonymous ; A western world with an eastern book ; The problem of Judaizing ; Diversity among early believers ; Not bound but free ; Judaizing in Bible times Paul and the Law ; Jewish heritage and today's Church --
Includes indexes
Includes bibliographical references (pages 338-346)
Keywords: Judaism -- Relations -- Christianity; Christianity and other religions -- Judaism; Christianity -- Origin